The Boyd Conjecture - Boyd, Jeffrey (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The Boyd Conjecture is that the amplitude of an elementary ray from the Theory of Elementary Waves (TEW) is the physical analog of a probability amplitude from Quantum Mechanics (QM). Boyd learned TEW from his cousin Lewis E. Little, who had said that quantum math is the roadmap to the world of elementary waves, but we did not know how to read the map. He suggested that Boyd, with a degree in mathematics, should work on deciphering the map. In 2014 Boyd began thinking that amplitudes are the core of QM, and elementary rays the core of TEW: perhaps they were equivalent. Both decisively influence particle behavior without conveying any energy. This essay discusses the history, strengths, weakness and implications of this conjecture.